2012
DOI: 10.1159/000338559
|View full text |Cite
|
Sign up to set email alerts
|

Opium Could Be Considered an Independent Risk Factor for Lung Cancer: A Case-Control Study

Abstract: Background: Lung cancer is the leading cause of cancer-related death worldwide, and half of all incident lung cancers are believed to occur in the developing countries, including Iran. Objective: We investigated the association of opium with the risk of lung cancer in a case-control study. Methods: We enrolled 242 cases and 484 matched controls in this study. A questionnaire was developed, containing questions on basic demographic characteristics, as well as lifelong history of smoking cigarettes, exposure to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
68
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(73 citation statements)
references
References 46 publications
(25 reference statements)
5
68
0
Order By: Relevance
“…The two previous epidemiological studies of opium in relation to laryngeal cancer7 8 had a retrospective case-control design and showed statistically significant increased risks, with ORs close to 10. Previous studies9 10 have also shown an increased risk of lung cancer, with relative risks of close to 2 or 3 in opium users. Our study results did not show statistically significant increased risks of lung cancer or laryngeal cancer in opium users, but the point estimates of the HRs were above 1 and consistent with the findings of the previous studies.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The two previous epidemiological studies of opium in relation to laryngeal cancer7 8 had a retrospective case-control design and showed statistically significant increased risks, with ORs close to 10. Previous studies9 10 have also shown an increased risk of lung cancer, with relative risks of close to 2 or 3 in opium users. Our study results did not show statistically significant increased risks of lung cancer or laryngeal cancer in opium users, but the point estimates of the HRs were above 1 and consistent with the findings of the previous studies.…”
Section: Discussionmentioning
confidence: 89%
“…Whereas a few other studies evaluating the carcinogenicity of opium appeared in the literature in the 1970s and early 1980s, there was a hiatus for nearly two decades, and most studies of opium and cancer have been published in the last 12 years 15. Epidemiological studies have associated opium use with increased risk of cancers of the oral cavity,14 16 larynx,7 8 lung,9 10 oesophagus,17–20 stomach20–23 and bladder 24–29. The two previous epidemiological studies of opium in relation to laryngeal cancer7 8 had a retrospective case-control design and showed statistically significant increased risks, with ORs close to 10.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regular use of opium has been reported to be associated with increased risk of several cancers, including esophageal cancer 9-11 , laryngeal cancer 12 , bladder cancer 13-15 , and lung cancer 16 , but to our knowledge no epidemiologic studies of opium use and gastric cancer have been published. About 0.3-0.5% of the world’s population in the 15-64 year old age group, between 12 and 21 million people, used opiates at least once in 2009 17 .…”
Section: Introductionmentioning
confidence: 96%
“…Use of opium and its derivatives has also been questioned as a factor (22). However, it has been proved as a risk factor for various cancers such as gastric (23,24), lung (25), larynx (26), bladder (27), and esophagus (24). Also, in a study in north of Iran, it was demonstrated that the level of morphine metabolites in the urine sample of patients in high risk regions for esophageal cancer was 6 times higher than in other regions (28).…”
Section: Introductionmentioning
confidence: 99%